How have Zambian businesses reacted to the HIV epidemic?. Issue 9 (September 1995) - Baggaley, R; Godfrey-Faussett, P; Msiska, R; Chilangwa, D; Chitu, E; Porter, J; Kelly, M
Abstract : OBJECTIVES–To evaluate the impact of HIV on businesses in Zambia and to assess attitudes towards HIV and HIV education in the workplace. METHODS–The personnel managers of 33 companies with a total workforce of 10, 204 in Lusaka and in towns in the Copperbelt were visited by two members of the study team. The study was discussed and a questionnaire about the impact of HIV on their company was explained and left for completion from company records. RESULTS–All 33 questionnaires were returned. HIV was recognised to be a problem by 30 companies questioned. Seven said that it had affected recruitment and 11 production. 23 companies carried out pre-employment medicals. 17 companies demanded that some or all of their employees had an HIV test before employment. Nine companies were sure that a positive HIV test would prevent employment, 15 were unsure saying that there was no particular company policy. Two companies had recently changed their policy and had stopped discriminating against those with HIV. 12 companies had some HIV educational material available for their employees and five had someone (or an organisation that they used) to whom they could refer employees for HIV information and advice. Condoms were provided free to staff by five of the companies. All thought that HIV education in the workplace was an appropriate intervention. Mortality data showed a sevenfold increase in the crude mortality from 0.25-1.8 per 100 person-years from 1987-93, and an increasing trend in reported deaths from AIDS and HIV related conditions. CONCLUSIONS–HIV is having an important impact in the workplace in urban Zambia. Although many companies insist on pre-employment medicals, often including HIV testing, few have developed policies relating to test results. Some companies have instituted HIV education but there is a demand for this service to be available more widely. There has been a striking increase in mortalities in this working population, which seems likely to be related to HIV, although the cause of most deaths was not recorded.